Effect of multi-wall carbon nanotubes on electrochemical performances of MnO2 - Rahul Singhal; Bhagirath Saini; Monica Kiehnle-Benitez; Thomas Sadowski; Christine Broadbridge; Jules Scanley; Peter K. LeMaire; Rakesh K. Sharma (AIP Advances, 2022)
Composites of MnO2/multi-wall carbon nanotubes (MWCNTs) were prepared using different weight ratios of MWCNTs: KMnO4 (1:2, 1:5, 1:10, 1:15, 1:20, and 1:25) using a one-pot hydrothermal method. The synthesized materials were physically characterized by x-ray diffraction, transmission electron microscopy (TEM), field emission-scanning electron microscopy (FE-SEM), (Brunauer–Emmett–Teller) BET, and thermogravimetric analysis. TEM and SEM studies indicate that MnO2 is homogeneously entangled with MWCNTs. The electrochemical performance evaluation was performed in a 3-electrode system using MnO2/MWCNT electrodes coated onto a Ni mesh as the working electrode, a Pt foil as the counter electrode, and Ag/AgCl as the reference electrode. The specific capacitance was obtained from charge–discharge studies at varying current densities between 0.5 and 5 A/g. The specific capacitance of MWCNT-KMnO4 (1:10, 1:15, and 1:25) samples was obtained as 114, 164, and 100 F/g, respectively, at a current density of 1 A/g.